Overcoming Repetition: Robotic Fabrication Processes at a Large Scale. (September 2013) - Hack, Norman; Lauer, Willi; Langenberg, Silke; Gramazio, Fabio; Kohler, Matthias
In the context of the Future Cities Laboratory (FCL) of ETH Zurich, the Professorship for Architecture and Digital Fabrication of Fabio Gramazio and Matthias Kohler has set up a robotic laboratory to investigate the potentials of non-standard robotic fabrication for high rise constructions in Singapore. The high degree of industrialisation of this dominant building typology implies standardisation, simplification and repetition and accounts for the increasing monotony evident in many Asian metropolises. The aim of this research on material systems for robotic construction is to develop a new and competitive construction method that makes full use of the malleable potential of concrete as a building material. A novel, spatial, robotic "weaving" method of a tensile active material that simultaneously acts as the form defining mould, folds two separate aspects of concrete -reinforcement and formwork-into one single robotic fabrication process (see Figure 1). This in-situ process could permit the fabrication of structurally differentiated, spatially articulated and material efficient buildings.